2016
DOI: 10.2147/cia.s97363
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of safety and efficacy of weekly nab-paclitaxel as second-line chemotherapy in elderly patients with advanced squamous non-small-cell lung carcinoma

Abstract: PurposeThe aim of this retrospective study was to investigate the anticancer effect and toxicity of weekly administered nab-paclitaxel as a second-line chemotherapy in elderly patients with relapsed squamous non-small-cell lung cancer (NSCLC).Patients and methodsWe retrospectively reviewed the treatment of 42 elderly patients with relapsed squamous NSCLC, who received nab-paclitaxel monotherapy as a second-line treatment from January 2010 to March 2014. A dose of 100 mg/m2 nab-paclitaxel was administered weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…3.6 months for ≥ third-line treatment; p = 0.78) [ 18 ]. The analysis in Chinese populations demonstrated that weekly administering Nab-PTX monotherapy (100 mg/m 2 on days 1, 8, and 15 of a 28-day cycle) as a second-line chemotherapy in elderly patients with squamous NSCLC was an effective and safe regimen for relapsed NSCLC in terms of ORR, DCR, PFS, and OS, regardless of prior taxane treatment according to the subgroup analysis ( p = 0.952) [ 20 ]. The median PFS in our study for patients with prior taxane treatment was similar to those without prior taxane treatment (median, 4.11 versus 4.54 months, p = 0.195).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3.6 months for ≥ third-line treatment; p = 0.78) [ 18 ]. The analysis in Chinese populations demonstrated that weekly administering Nab-PTX monotherapy (100 mg/m 2 on days 1, 8, and 15 of a 28-day cycle) as a second-line chemotherapy in elderly patients with squamous NSCLC was an effective and safe regimen for relapsed NSCLC in terms of ORR, DCR, PFS, and OS, regardless of prior taxane treatment according to the subgroup analysis ( p = 0.952) [ 20 ]. The median PFS in our study for patients with prior taxane treatment was similar to those without prior taxane treatment (median, 4.11 versus 4.54 months, p = 0.195).…”
Section: Discussionmentioning
confidence: 99%
“…While we found that Nab-PTX was most often prescribed as second-line or later treatment in clinic. Although a few studies [ 18 20 ] had reported that Nab-PTX as second line or later regimen of chemotherapy was effective in advanced NSCLC among Western populations and East Asia populations, and there was no significant difference, regardless of prior taxane treatment. While there has been no a standard usage of Nab-PTX for these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the ORR and DCR were 26.5% and 82.4%, respectively; the median PFS and OS were 6.0 and 11.0 months, respectively. Previous studies of nab-PTX alone in second or further line treatment of NSCLC reported a PFS of 3.5-6.6 months and an OS of 6.8-15.7 months, with ORRs ranging from 16.1%-35.5% 27 , 28 , 37 - 40 . A study of nab-PTX combined with carboplatin reported a PFS of 4.0 months and an OS of 14.0 months 41 .…”
Section: Discussionmentioning
confidence: 97%
“…There are data regarding second line treatment with nab-paclitaxel as second line treatment for the elderly, however; there are no data regarding whether it could be used as first line treatment. 8 Moreover; there are recently published data regarding the efficacy of nab-paclitaxel in combination with carboplatin for non-small cell lung cancer. 9 Nab-paclitaxel belongs to the taxane family, however; it is designed in a so that it has a local sustain release effect and deep penetration in tumor tissue.…”
Section: Introductionmentioning
confidence: 99%